2020
DOI: 10.1016/j.compag.2020.105640
|View full text |Cite
|
Sign up to set email alerts
|

Discovering weather periods and crop properties favorable for coffee rust incidence from feature selection approaches

Abstract: Coffee Leaf Rust (CLR) is a disease that leads to considerable losses in the worldwide coffee industry; as those that have been reported recently in Colombia and Central America. The early detection of favorable conditions for epidemics could be used to improve decision making for the coffee grower and thus reduce the losses due to the disease. Researchers tried to predict the occurrence of the disease earlier through statistical and machine learning models from crop properties, disease indicators and weather … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 52 publications
0
12
0
1
Order By: Relevance
“…The difference found at the provincial level could be associated with the shade used in each location since it has been shown that this could have antagonistic effects on coffee rust ( López-Bravo et al., 2012 ). In addition, climatic variables such as temperature, which is a determining factor for the germination and penetration phases of the fungus, precipitation, which contributes to dispersal conditions and the washing of uredospores, and relative humidity also play a role ( Lasso et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The difference found at the provincial level could be associated with the shade used in each location since it has been shown that this could have antagonistic effects on coffee rust ( López-Bravo et al., 2012 ). In addition, climatic variables such as temperature, which is a determining factor for the germination and penetration phases of the fungus, precipitation, which contributes to dispersal conditions and the washing of uredospores, and relative humidity also play a role ( Lasso et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…1 Unlike temperatures, precipitations have an ambiguous impact on CLR. The disease seems to be favored by wetness but is washed-off by intense rainfall (Merle et al, 2020;Lasso et al, 2020). The timing of precipitations also matters, as suggested by Avelino et al (2015) who observe positive early rainfall anomalies before the CLR epidemic in Guatemala, Honduras, and Nicaragua.…”
Section: The 2012 Coffee Leaf Rust Epidemicmentioning
confidence: 89%
“…The detailed process of this modeling, as well as the analysis of the results was published in [57]. Next we will present a summary of the results, framing them in the DM phases of FramePests.…”
Section: ) Data-based Modeling (Dm) Of Clrmentioning
confidence: 99%
“…We relied on the weather 14 days before DP, similar to KM. We used the concept of time windows [29], [57] to generate consecutive subperiods of each climatic variable within the main period of 14 days before DP.…”
Section: ) Data-based Modeling (Dm) Of Clrmentioning
confidence: 99%
See 1 more Smart Citation